Clinical Features and Outcomes of Coronavirus Disease 2019 in Patients with Inflammatory Bowel Disease and Spondyloarthropathies - Tozlu, Mukaddes; Dilek, Gamze; Kalçık Unan, Mehtap; Kamanlı, Ayhan; Tekeoğlu, İbrahim and Uslan, Mustafa İhsan and Nas, Kemal (Turkish Journal of Gastroenterology, 2022)
Background: We aimed to determine the clinical features, predictive factors associated with severe disease, and outcomes of coronavirus disease 2019 in patients with immune-mediated inflammatory diseases and report data on the comparison of coronavirus disease 2019 between patients with inflammatory bowel disease and spondyloarthropathies. Methods: A total of 101 patients with inflammatory bowel disease and spondyloarthropathies who had confirmed diagnosis of coronavirus disease 2019 were retrospectively analyzed. Demographics, comorbidities, immunosuppressive treatments, and the impact of immunosuppression on negative outcomes were assessed. Results: The median age of the patients was 47 (38-57) years. The most common rheumatologic diagnosis was ankylosing spondylitis (n = 24), psoriatic arthritis (n = 17), and reactive arthritis (n = 1). In the inflammatory bowel disease group, 47 patients had ulcerative colitis, 11 Crohn’s disease, and 1 unclassified. The most commonly used treatments were biologics (55%) in the spondyloarthropathies group and aminosalicylates (66.1%) in the inflammatory bowel disease group. Overall, 18.8% of the patients required hospitalization, 5% developed severe complications, and 2% died. There were no significant differences in coronavirus disease 2019-related negative outcomes between spondyloarthropathies and inflammatory bowel disease patients. The median age was higher in the patients who required hospitalization [57 (46-66) vs 47 (38-57) years, P=.008]. Bilateral opacities on chest radiographs were more common in the patients who required hospitalization in the spondyloarthropathies group [88.9% vs 14.3%, P=.016]. Comorbidity was significantly associated with hospitalization in the inflammatory bowel disease group (P ≤ .05). Baseline therapy with biologics or immunosuppressives was not associated with severe coronavirus disease 2019 outcomes. Conclusion: Older age, comorbidities, and bilateral ground-glass opacities were associated with adverse outcomes, whereas specific immune-mediated inflammatory disease diagnoses or immunosuppressive treatments were not. Cite this article as: Tozlu M, Dilek G, Kalçık Unan M, et al. Clinical features and outcomes of coronavirus disease 2019 in patients with inflammatory bowel disease and spondyloarthropathies. Turk J Gastroenterol. 2022;33(9):751-759.